The Influence of Socioeconomic Status on Executive Functions: Causal Study in Kindergarten Group B DKI Jakarta Province in 2024 - Susanti, Debie (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
This study aims to examine the influence of socioeconomic status on executive function in Kindergarten children (Group B) in the DKI Jakarta Province in 2024. Using a quantitative causal associative approach with a survey method and path analysis technique, this research involved 102 students selected through multistage cluster random sampling. Data were collected using a modified BRIEF-P instrument to measure executive function and a questionnaire to assess socioeconomic status. The results indicate a significant favorable influence of socioeconomic status on children's executive function (path coefficient 0.358, t-value 5.47). Children with higher socioeconomic status tend to have better executive functions. These findings highlight the importance of interventions to improve executive function, particularly for children from lower socioeconomic backgrounds, to support their future academic success. This research provides valuable insights for developing more inclusive and equitable early childhood education policies.